Natural fiber reinforced composites: Sustainable materials for emerging applications - Muhammad Yasir Khalid (17052429) (2021)
In the contemporary world, natural fibers reinforced polymer composite (NFRPC) materials are of great interest owing to their eco-friendly nature, lightweight, life-cycle superiority, biodegradability, low cost, noble mechanical properties. NFRPCs are widely applied in various engineering applications and this research field is continuously developing. However, the researchers are facing numerous challenges regarding the developments and applications of NFPRCs due to the inherent characteristics of natural fibers (NFs). These challenges include quality of the fiber, thermal stability, water absorption capacity, and incompatibility with the polymer matrices. Ecological and economic concerns are animating new research in the field of NFRPCs. Furthermore, considerable research is carried out to improve the performance of NFRPCs in recent years. This review highlights some of the important breakthroughs associated with the NFRPCs in terms of sustainability, eco-friendliness, and economic perspective. It also includes hybridization of NFs with synthetic fibers which is a highly effective way of improving the mechanical properties of NFRPCs along with some chemical treatment procedures. This review also elucidates the significance of using numerical models for NFRPCs. Finally, conclusions and recommendations are drawn to assist the researchers with future research directions. Other Information Published in: Results in Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rineng.2021.100263